2015
DOI: 10.1007/s00701-015-2390-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the thioredoxin system during subarachnoid hemorrhage-induced cerebral vasospasm

Abstract: The Trx system seems to be negatively affected by the simultaneously interrelated enzymatic alterations during cerebral vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Several studies recently reported that TXNIP plays dual pro-inflammatory and pro-apoptotic roles in ischaemic diseases [23, 39], but the relationship between TXNIP and SAH has not been elucidated. Kaya and colleagues reported that SAH induced TXNIP mRNA expression [40]. Therefore, we speculated that TXNIP may also participate in the pathogenesis of EBI.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies recently reported that TXNIP plays dual pro-inflammatory and pro-apoptotic roles in ischaemic diseases [23, 39], but the relationship between TXNIP and SAH has not been elucidated. Kaya and colleagues reported that SAH induced TXNIP mRNA expression [40]. Therefore, we speculated that TXNIP may also participate in the pathogenesis of EBI.…”
Section: Discussionmentioning
confidence: 91%
“…Nonenzymatic antioxidants are an important class of antioxidants that play important roles in the pathogenesis of cerebral hemorrhage. These include glutathione [ 53 , 109 ], antioxidant vitamins [ 106 , 110 ], uric acid [ 111 ], ubiquinone-reducing substances [ 54 , 112 ], metallothionein [ 113 ], and thioredoxin system [ 114 , 115 ]. However, methods for the detection of oxidative stress related nonenzymatic antioxidants in the peripheral blood are few; one study on the level of glutathione (GSH) in umbilical cord blood after neonatal periventricular hemorrhage found that cord blood GSH level was not related to intraventricular hemorrhage in low-birthweight neonates [ 116 ].…”
Section: Detection Of the Level Of Oxidative Stressmentioning
confidence: 99%
“…Studies have found that TOS and NO serum levels in patients are significantly increased after cerebral hemorrhage, while TAC levels and catalase activity are significantly reduced. Therefore, the oxidative stress index (OSI) is increased [ 115 , 127 ].…”
Section: Detection Of the Level Of Oxidative Stressmentioning
confidence: 99%
“…According to several reports, increased mRNA expression of TXNIP has been also detected in brains affected with sub-arachnoid hemorrhage (SAH) [130, 131]. In a rabbit model of SAH, the brain stem levels of TRX1 and TRX reductase (TRXR) decreased in parallel with a rise in the expression of TXNIP [130].…”
Section: Introductionmentioning
confidence: 99%